2018
DOI: 10.3390/ijms19103011
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Reveals Novel Genomic Regions for Grain Yield and Yield-Related Traits in Drought-Stressed Synthetic Hexaploid Wheat

Abstract: Synthetic hexaploid wheat (SHW; 2n = 6x = 42, AABBDD, Triticum aestivum L.) is produced from an interspecific cross between durum wheat (2n = 4x = 28, AABB, T. turgidum L.) and goat grass (2n = 2x = 14, DD, Aegilops tauschii Coss.) and is reported to have significant novel alleles-controlling biotic and abiotic stresses resistance. A genome-wide association study (GWAS) was conducted to unravel these loci [marker–trait associations (MTAs)] using 35,648 genotyping-by-sequencing-derived single nucleotide polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
99
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 92 publications
12
99
3
Order By: Relevance
“…We also found MTAs associated with drought stress. Moreover, we found several other MTAs whose annotations suggest different roles including response to drought stress (TBC1 domain family member, SNF1-related protein kinase regulatory subunit beta-2) plant senescence (E3 ubiquitin-protein ligase ORTHRUS 2), salt stress (Glutamyl-tRNA (Gln) amidotransferase subunit A), disease resistance (Disease resistance protein (NBS-LRR class) family), metabolism (Adenosine kinase-like protein) and antioxidant defense (Telomere repeat-binding factor like-protein) [30][31][32][33][34][35][36]. Our study identified novel MTAs associated with SPAD measurements in US soft wheat under HT conditions which contributes to a better understanding of the genetic basis of SPAD traits in wheat.…”
Section: Discussionmentioning
confidence: 99%
“…We also found MTAs associated with drought stress. Moreover, we found several other MTAs whose annotations suggest different roles including response to drought stress (TBC1 domain family member, SNF1-related protein kinase regulatory subunit beta-2) plant senescence (E3 ubiquitin-protein ligase ORTHRUS 2), salt stress (Glutamyl-tRNA (Gln) amidotransferase subunit A), disease resistance (Disease resistance protein (NBS-LRR class) family), metabolism (Adenosine kinase-like protein) and antioxidant defense (Telomere repeat-binding factor like-protein) [30][31][32][33][34][35][36]. Our study identified novel MTAs associated with SPAD measurements in US soft wheat under HT conditions which contributes to a better understanding of the genetic basis of SPAD traits in wheat.…”
Section: Discussionmentioning
confidence: 99%
“…One approach which can facilitate a more accurate estimation for the improvement of trait stability is through examining the genetic architecture underlying stability and implementing genomic-assisted breeding [4,5]. Genetic mapping through association studies and genomic selection has been widely used to dissect the architecture of important traits in wheat (Triticum aestivum L.) [6][7][8][9]. A genomewide association study (GWAS) identifies genetic loci linked to phenotypic values of trait variation through…”
Section: Introductionmentioning
confidence: 99%
“…In case of exceeding the relative air humidity inside with respect to the relative air humidity outside, it is recommended to provide ventilation above the grain [4], otherwise the quality of the stored products will be reduced.…”
Section: Resultsmentioning
confidence: 99%
“…The main method of storage in metal containers, according to the instructions [1,2] and safety regulations is the storage of grain in a dry and purified state [3]. It is known that not only humidity and purity, but also the temperature of the grain put into storage affect the storage period [4]. The lower the temperature, the longer the storage time becomes.…”
Section: Introductionmentioning
confidence: 99%